A Novel Mobile Element ICERspD18B in Rheinheimera sp. D18 Contributes to Antibiotic and Arsenic Resistance - Fu, Jiafang; Zhong, Chuanqing; Zhang, Peipei; Gao, Qingxia; Zong, Gongli; Zhou, Yingping; Cao, Guangxiang (Frontiers in Microbiology, 2020)
Antibiotics and organoarsenical compounds are frequently used as feed additives in many countries. However, these compounds can cause serious antibiotic and arsenic pollution in the environment, and the spread of antibiotic and arsenic resistance genes from the environment. In this report, we characterized the 28.5 kb genomic island, named as ICERspD18B, as a novel chromosomal integrative and conjugative element in multidrug-resistant Rheinheimera sp. D18. Notably, ICERspD18B contains six antibiotic resistance genes and an arsenic tolerance operon, as well as genes encoding conjugative transfer proteins of a type IV secretion system, relaxase, site-specific integrase and DNA replication or partitioning proteins. The transconjugant strain 25D18-B4 was generated using Escherichia coli 25DN as the recipient strain. ICERspD18B was inserted into 3’-end of the guaA gene in 25D18-B4. In addition, 25D18-B4 had markedly higher minimum inhibitory concentrations for arsenic compounds and antibiotics when compared to the parental E. coli strain. These findings demonstrated that the integrative and conjugative element ICERspD18B could mediate both antibiotic and arsenic resistance in Rheinheimera sp. D18 and the transconjugant 25D18-B4.